(3TQM GdCSHGH hGdYdGeGJ ddSeQbfOis - (3HQgGf GdOjf fajS Hf YhV Hf Mcje GdcQeGfis; (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3CMeO Hf CHj HcQ Ydi GHf GdbUGQ s)
(3ChdgG (B:s
(3hcGf bSe GdCeQGV GdLRFjI ef gPG Gdaf de jbUO CMO ef GdCaGVd Edi GdCf dJaSjQg hJTQjMg aCQOJ Cf CcTa Yf hLhg ahGFO gPG Gdaf s
(3BNQgG (B:s
(3hCf jbJUQ Ydi eKd LhR GdSQ hGdCHgd , hSGFQ eG jfaY ai VeGO GdaJb aEfgG JTO GdYVh hJfTa GdQWhHGJ s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs